2008
DOI: 10.1139/h08-125
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations of erythrocyte membrane components induced by exhaustive exercise

Abstract: Physical exercise was used as a model of the physiological modulator of free radical production to examine the effects of exercise-induced oxidative modifications on the physico-biochemical properties of erythrocyte membrane. The aim of our work was to investigate conformational changes of erythrocyte membrane proteins, membrane fluidity, and membrane susceptibility to disintegration. Venous blood was taken before, immediately after, and 1 h after an exhaustive incremental cycling test (30 W.min-1 ramp), perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 37 publications
0
32
0
4
Order By: Relevance
“…Similar observations, rigidity in erythrocyte membranes, were found in four sedentary dogs after submaximal exercise in a study attempting to elucidate the role of vitamin E supplementation in preventing the effects of submaximal exercise-induced oxidative damage over a long period of time (Motta et al 2009). Finally, Brzeszczynska et al (2008) detected erythrocyte rigidity 1 h after an exhaustive incremental cycling test performed in 11 healthy untrained males. These authors employed three spin labels, 5-, 12-or 16-doxylstearic acids to provide information of changes in the microenvironment in the nearest region of different depths of membrane bilayers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations, rigidity in erythrocyte membranes, were found in four sedentary dogs after submaximal exercise in a study attempting to elucidate the role of vitamin E supplementation in preventing the effects of submaximal exercise-induced oxidative damage over a long period of time (Motta et al 2009). Finally, Brzeszczynska et al (2008) detected erythrocyte rigidity 1 h after an exhaustive incremental cycling test performed in 11 healthy untrained males. These authors employed three spin labels, 5-, 12-or 16-doxylstearic acids to provide information of changes in the microenvironment in the nearest region of different depths of membrane bilayers.…”
Section: Discussionmentioning
confidence: 99%
“…These authors employed three spin labels, 5-, 12-or 16-doxylstearic acids to provide information of changes in the microenvironment in the nearest region of different depths of membrane bilayers. Since an increase in the order was detected only for the 5-doxylstearic acid spin label, they concluded that exercise-induced decreases in erythrocyte membrane fluidity were located in the polar region of the membranes (Brzeszczynska et al 2008). To measure fluidity changes in this specific region of the membrane, we chose TMA-DPH because the polar region of this probe is anchored at the lipid-water interface, while the hydrocarbon moiety enters the lipid part of the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We think that RBC destruction is one important reason leading to anemia [15,16] . The cause of RBC destruction is discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Он наступает вcледствие нарушения баланса между образованием и удалeнием активированных кислородных интермедиатов -таких, как пероксид водорода (H 2 O 2 ), супероксидный анион (O 2 -) и другие радикалы. Результатом окислительного повреждения мембранных белков и липидов является снижение текучести клеточной мембраны эритроцита [4]. Выявлено антиокислительное действие ингибиторов 3-гидрокси-3-метилглутарил-CoA-редуктазы (КФ 1.1.1.88) (статинов), не зависящее от их гипохолестеринемического влияния [5].…”
unclassified